2010
DOI: 10.1111/j.1749-7345.2009.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Heat‐killed Lactobacillus plantarum on Larval and Post‐larval Kuruma Shrimp, Marsupenaeus japonicus Bate

Abstract: Two feeding trials were conducted to evaluate the effects of heat‐killed Lactobacillus plantarum (HK‐LP) on larval and post‐larval kuruma shrimp, Marsupenaeus japonicus Bate. Five microbound diets were formulated to contain levels of a preparation containing 20% HK‐LP (HK‐LP Prep): 0, 0.001, 0.01, 0.1, and 1 g/kg. In the first experiment, zoea1 stage larvae were fed test diets for 8 d. Some parameters such as survival, developmental stage, metamorphosis to post‐larvae, and formalin stress resistance were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…Diet supplemented with HK L‐137 was reported to improve the growth performance of Kuruma shrimp (Thanh Tung et al . ). Enhanced growth performances for supplemented probiotics were also observed in shrimp (Rengpipat, Phianphak, Piyatiratitivorakul & Menasveta ; Wang ) and fish (Yanbo & Zirong ; Ziaei‐Nejad et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Diet supplemented with HK L‐137 was reported to improve the growth performance of Kuruma shrimp (Thanh Tung et al . ). Enhanced growth performances for supplemented probiotics were also observed in shrimp (Rengpipat, Phianphak, Piyatiratitivorakul & Menasveta ; Wang ) and fish (Yanbo & Zirong ; Ziaei‐Nejad et al .…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that HK L‐137 may be effective in responses of growth and biological defence systems of larval and post‐larval Kuruma Shrimp (Thanh Tung et al . ). In the light of these observations, it was assumed that HK L‐137 may be effective in growth digestive, non‐specific immune and phosphatase of sea cucumbers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mortality was monitored every 5 min. Survival was expressed as the cumulative mortality index (CMI) and calculated as the average value of cumulative survival obtained from each replicate diet in relation to the experimental time (Tung, Koshio, Traifalgar, Ishikawa, & Yokoyama, 2010). A lower value indicates greater tolerance to the stressors.…”
Section: Stress Resistance Testmentioning
confidence: 99%
“…Fish and shrimp fed on supplemented feed with live, dead, cell‐free extract and fermentation supernatant L . plantarum enhanced in the innate immunity (stimulating pro‐inflammatory cytokines, activity of natural killer cells, antibody production, lysozyme and phagocytosis) and disease resistance (Giri et al., 2013; Son et al., 2009; Thanh Tung et al., 2010).…”
Section: Introductionmentioning
confidence: 99%